Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.3* The Natural Exponential Function - 6.3* Exercises: 49

Answer

$g'(u)=ue^{\sqrt secu^{2}}(\sqrt secu^{2})(tanu^{2})$

Work Step by Step

$g'(u)=\frac{d}{du}(e^{\sqrt secu^{2}})$ $=e^{\sqrt secu^{2}}\frac{d}{du}({\sqrt secu^{2}})$ $=e^{\sqrt secu^{2}}\frac{1}{2(\sqrt secu^{2})}\frac{d}{du}({secu^{2}})$ $=e^{\sqrt secu^{2}}\frac{1}{2(\sqrt secu^{2})}({secu^{2}})({tanu^{2}}).2u$ Hence, $g'(u)=ue^{\sqrt secu^{2}}(\sqrt secu^{2})(tanu^{2})$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.